2007
DOI: 10.17705/1jais.00121
|View full text |Cite
|
Sign up to set email alerts
|

Post-positivist Review of Technology Acceptance Model.

Abstract: This paper reflects upon the technology acceptance model (TAM) from the perspective of the post positivistic philosophy of science. I explore what it is to know, what a theory is, and what it means to be scientific in the context of TAM. In particular, I review criteria for determining whether TAM is scientific or not in light of post-positivistic debates about the nature of science. For this purpose, I apply Popper's principle of demarcation, which determines whether a theory-like TAM-is falsifiable and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 28 publications
0
88
0
1
Order By: Relevance
“…The literature is divided (Silva 2007); some explain that there is a direct relationship between firms' dynamic capabilities and their performance or competitive advantage (Makadok 2001;Zollo and Winter 2002). Others have linked dynamic capabilities to competitive advantage but have asserted that this link is indirect (Zott 2003;Helfat and Peteraf 2003;Ambrosini and Bowman 2009;Wang and Ahmed 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature is divided (Silva 2007); some explain that there is a direct relationship between firms' dynamic capabilities and their performance or competitive advantage (Makadok 2001;Zollo and Winter 2002). Others have linked dynamic capabilities to competitive advantage but have asserted that this link is indirect (Zott 2003;Helfat and Peteraf 2003;Ambrosini and Bowman 2009;Wang and Ahmed 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the research setting where the studied organizations operate in a business-to-business environment, the survey research and statistical techniques often used in IT adoption studies (e.g. Silva 2007) might suffer from the large number of contextual variables influencing organizational behavior (Johnston et al, 1999) suggesting that explanatory qualitative approach with interviews suits well for this study in hand.…”
Section: Methodsmentioning
confidence: 99%
“…A number of research critique papers on TAM have been published in recent years (e.g. Bagozzi [4], Benbasat and Barki [5], Hirschheim [7], King and He [9], Legris et al [10], Schwarz and Chin [1], Silva [12] and Venkatesh et al [13]). However, a more detailed examination revealed that TAM was the most popular theory in examining the ICTs adoption.…”
Section: B Theoriesmentioning
confidence: 99%
“…A number of attempts are made to provide a comprehensive review of the trends and issues in ICTs adoption research (e.g. Bagozzi [4], Benbasat and Barki [5], Choudrie and Dwivedi [6], Hirschheim [7], Jeyaraj et al [8], King and He [9], Legris et al [10], Lucas et al [11], Schwarz and Chin [1], Silva [12] and Venkatesh et al [13]). but each of them seems to have limitations in its own right.…”
Section: Introductionmentioning
confidence: 99%